An Examination of Mental Toughness, Perceived Effort, and Selected Fundamental Technical Skills in Children Aged 11–14 Receiving Taekwondo Training - Hepsert, Sezgin; Sezer, Burcu Sıla; Genç, Harun; Kılıç, Yakup; Özer, Hasan (METİN YAMAN, 2026)
This study aimed to investigate the effects of taekwondo training on perceived exertion, mental endurance, and technical skills in children aged 11–14 years. The study was conducted using a pre-test-post-test control group quasi-experimental design. Participants were divided into two groups: experimental (n=8) and control (n=8). The experimental group underwent agility and speed training in addition to taekwondo techniques three days a week for eight weeks, while the control group only underwent technical training. Physical fitness was assessed using the Paldinj, Dutchaji, and Dolye Chali techniques, while mental endurance and perceived exertion levels were measured using scales. Statistical analyses were performed using SPSS software. The normality of the data was assessed using skewness and kurtosis values. Paired samples t-tests were used for intra-group comparisons, while independent samples t-tests were used for inter-group comparisons. GraphPad Prism 8 software was also used for visualisation. According to the research results, significant increases were observed in mental resilience and technical skills (Paldinj, Dutchaji, Dolye Chali) in the experimental group (p0.05). The findings show that taekwondo training is effective in improving children's technical development as well as their mental resilience. However, the lack of change in perceived effort suggests that subjective assessment scales may have limited sensitivity in children. In conclusion, it can be said that taekwondo plays an important role in the physical and psychological development of children, and can be an effective tool in supporting mental resilience in particular. It is recommended that coaches and educators consider both physical performance and psychological resilience factors when planning training programmes for child athletes. Future studies with larger samples, different age groups, and long-term interventions would be beneficial.

Bu çalışma, 11-14 yaş arası çocuklarda taekwondo eğitiminin algılanan efor, zihinsel dayanıklılık ve teknik beceriler üzerindeki etkilerini incelemeyi amaçlamıştır. Araştırma, ön test-son test kontrol gruplu yarı deneysel desenle gerçekleştirilmiştir. Katılımcılar, deney (n=8) ve kontrol (n=8) olmak üzere iki gruba ayrılmıştır. Deney grubuna 8 hafta boyunca haftada üç gün taekwondo tekniklerine ek olarak çeviklik-sürat çalışmaları uygulanırken, kontrol grubuna yalnızca teknik antrenmanlar yaptırılmıştır. Fiziksel uygunluk Paldinj, Dutchaji ve Dolye Chali teknikleriyle değerlendirilmiş; zihinsel dayanıklılık ve algılanan efor düzeyleri ölçeklerle ölçülmüştür. İstatistiksel analizler SPSS programında yapılmıştır. Verilerin normalliği çarpıklık ve basıklık değerleri ile değerlendirilmiştir. Grup içi karşılaştırmalarda eşleştirilmiş örneklemler t-testi (paired samples t-test), grup karşılaştırmalarında ise bağımsız örneklemler t-testi (independent samples t-test) kullanılmıştır. Ayrıca görselleştirme işlemleri için GraphPad Prism 8 yazılımından yararlanılmıştır. Araştırma sonuçlarına göre, deney grubunda zihinsel dayanıklılık ve teknik becerilerde (Paldinj, Dutchaji, Dolye Chali) anlamlı artışlar görülmüş (p0.05). Bulgular, taekwondo eğitiminin çocukların teknik gelişiminin yanı sıra zihinsel dayanıklılıklarını artırmada da etkili olduğunu göstermektedir. Buna karşın algılanan eforun değişmemesi, subjektif değerlendirme ölçeklerinin çocuklarda sınırlı hassasiyetle çalışabileceğini ortaya koymuştur. Sonuç olarak, taekwondo sporunun çocukların fiziksel ve psikolojik gelişiminde önemli bir rol oynadığı, özellikle zihinsel dayanıklılığın desteklenmesinde etkili bir araç olabileceği söylenebilir. Antrenör ve eğitimcilerin, çocuk sporcuların antrenman planlamasında hem fiziksel performans hem de psikolojik dayanıklılık faktörleri birlikte göz önünde bulundurmaları önerilmektedir. Gelecek çalışmalarda daha büyük örneklemlerle, farklı yaş gruplarında ve uzun süreli müdahalelerle benzer araştırmalar yapılması faydalı olacaktır.
Taekwondo Eğitimi Alan 11-14 Yaş Arası Çocuklarda Zihinsel Dayanıklılık, Algılanan Efor ve Bazı Temel Teknik Becerilerin İncelenmesi
Keywords: Sports Training; Antrenman